Volleyball serves impact sound intensity and frequency spectrum affect the predictions of the future ball's landing point according to the level of auditory-motor experience. - Camponogara, Ivan; Murgia, Mauro; D'Orso, Geremia; Sors, Fabrizio (International Journal of Sport & Exercise Psychology, 2024)
In ball sports, such as volleyball or soccer, the impact sound of the ball is used to define the shot length and predict the final ball position on the field. Several studies thoroughly investigated the role of sound intensity in predicting the ball's landing point, neglecting the equally important contribution of the sound frequency spectrum component. Here, we investigated the contribution of the sound frequency spectrum in defining a volleyball serve's length (i.e., distance). We recorded the sound of short and long volleyball serves (ecological sound) and changed their frequency spectrum in pink noise, preserving their intensity (noise sound). We then presented both sounds (ecological and noise) to expert volleyball players and measured their performance in short and long-shot classifications. The role of auditory-motor experience in sound classification was also explored by testing soccer players (experience on ball shots but not sport-specific auditory-motor experience) and non-athletes (no auditory-motor experience in sports). We found that hearing ecological sound leads to better sound discrimination performance than noise sound. Concurrently, we found an effect of the specific auditory-motor experience, with volleyball players outperforming non-athletes and soccer players. Interestingly, experts in different sports domains (soccer players) mainly used sound intensity for shot classification. This underlines the importance of specific auditory-motor experience in encoding specific sound frequency spectrum for the sound of action classification.